E-MONEY EMPOWERMENT FOR STUDENTS OF CLASS VII JA'FAR MUSLIM MUSLIM LINGGA TIGA MIDDLE SCHOOL AS GENERATION Z - Hasibuan, Habibur Rahman; Pristiyono, Pristiyono; Nasution, Meisa Fitri (LPPM Univ. Ibn Khaldun Bogor, 2022)
Habibur Rahman Hasibuan 1, Pristiyono2, Meisa Fitri Nasution3 faculty of Economics and Business Labuhanbatu University, Indonesia 1*habibhasibuan1098@gmail.com , paktio16@gmail.com2 , meisa.fitri@gmail.com3 Abstract This community service is about introducing e-money for students in facilitating payments in the digital era. According to Bank Indonesia, e-money is a payment system in a transaction through electronic media . The results obtained from this community service are that the delivery of the material carried out increases the understanding and knowledge of participants about e-money, previously 90% of students did not know about e-money then 95% of them were interested in using e-money. The data obtained from this community service is by distributing questionnaires to participants at the end of delivering the material. With this community service, it is hoped that the seventh grade students of Ja'far Muslim Lingga Tiga Muslim Middle School can increase their knowledge of e-money and are expected to provide education and understanding about e-money to those closest to them.